2019
DOI: 10.3389/fonc.2019.01149
|View full text |Cite
|
Sign up to set email alerts
|

Canmei Formula Reduces Colitis-Associated Colorectal Carcinogenesis in Mice by Modulating the Composition of Gut Microbiota

Abstract: The gut microbiota, including pathogenic microorganisms and probiotics, has been involved in tumor initiation and progression by regulating the components of intestinal flora. Canmei formula (CMF), a traditional Chinese medicine, chronicled in the Chuang Yang Jing Yan Quan Shu, has been clinically used as an adjuvant therapy to treat patients with colorectal carcinoma (CRC) in China. In this study, we investigate the treatment effect of CMF in the azoxymethane (AOM) and dextran sodium sulfate (DSS) induced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This formulation was shown to decrease the incidence of colonic tumors by reducing inflammation and improving dysbiosis. 137 Another study using a Boswellia serrata resin extract has also demonstrated, in preclinical models, its ability to reduce colonic tumor formation. 144 Many of these studies present positive results for the inhibition of CRC development.…”
Section: Discussionmentioning
confidence: 98%
“…This formulation was shown to decrease the incidence of colonic tumors by reducing inflammation and improving dysbiosis. 137 Another study using a Boswellia serrata resin extract has also demonstrated, in preclinical models, its ability to reduce colonic tumor formation. 144 Many of these studies present positive results for the inhibition of CRC development.…”
Section: Discussionmentioning
confidence: 98%
“… 19 Another TCM formula, CanMei formula, was found to upregulate the abundance of the genera Alistipes, Faecalibaculum, Lactobacillus , and Parabacterioides , while decreasing Desulfovibrionacea in colitis-associated colorectal tumor model mice, which might be associated with suppression of IL-17C and NF-κB to prevent CRC development. 20 Yang et al found that Ganoderma Lingzhi, a TCM herb, could reduce Clostridium coccoides and Clostridium leptum , and increase Akkermansia muciniphila in rats fed high-fat diets and could reduce production of secondary bile acids, which is important to CRC. 21 These findings provide important knowledge suggesting that different TCM herbal medicines could modulate certain gut bacteria and impact CRC development or treatment effect through immune, anti-inflammatory, or metabolic mechanisms, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…All the drugs prepared above were stored in a refrigerator at 4°C and shaken well before intragastric administration. The above drug extraction process was completed by the Pharmaceutical Research Room of Yueyang Hospital affiliated to Shanghai University of traditional Chinese Medicine ( Zhang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…To identify the components of Mume Sieb and Marci Hieronymi extract, Q Exactive high-performance benchtop quadrupole-Orbitrap LC-MS/MS was performed. The main components in the extract of CMF were identified according to the elemental composition data determined from accurate mass measurements and comparison with the literature data (this step was completed by our research group in the previous study) ( Zhang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation